Iowa RBA, April 29, 1996 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for April 29, 1996. Highlights of the update include sightings of White-faced Ibis, Little Blue Heron, Piping Plover, Red-necked Phalarope, Marbled Godwit and a White-winged Scoter. Also included are handwritten notes for the next week's update with sightings of Willets, Stilt Sandpipers and a Long-billed Dowitcher. Epson - sheet feed/flatbed